The science and politics of race in Mexico and the United States, 1910-1950 - Rosemblatt, Karin Alejandra (The University of North Carolina Press, 2018)
"In this history of the social and human sciences in twentieth-century Mexico and the United States, Karin Alejandra Rosemblatt reveals the intricate connections among the development of science, the concept of race in North America, and policy toward Indigenous peoples. Her focus is on the anthropologists, sociologists, biologists, physicians, and other experts who collaborated across borders in the midst of the Mexican Revolution through World War II, a period that saw a dynamic academic growth on both sides of the Rio Grande. Rosemblatt traces how these intellectuals forged shared networks in which they discussed Indigenous peoples and other ethnic minorities, refashioning race as a scientific category and consolidating their influence within their respective national policy circles"--